Quantitative analysis of γH2AX reveals distinct responses in multiple mouse organs after administration of mitomycin C or ethyl methanesulfonate. (24th December 2018) - Matsuda, Shun; Wanibuchi, Sayaka; Kasahara, Toshihiko
Abstract: Ser139-phosphorylated H2AX (γH2AX) is a functional biomarker of DNA double-strand breaks. However, its conventional detection for in vivo samples relies on immunological methods using anti-γH2AX antibodies, making quantitative analysis difficult. Here, we established an absolute γH2AX quantification in vivo method for multiple organs in mice using liquid chromatography–triple quadrupole tandem mass spectrometry. When applying the method to male Institute of Cancer Research (ICR) mice (8 weeks old), the testes showed the highest γH2AX level (2.3% of total H2AX), followed by the bone marrow (0.51%), stomach (0.28%), kidney (0.20%), spleen (0.20%), liver (0.15%) and lung, which had the lowest overall level (0.10%). After intraperitoneal administration of 2 mg/kg mitomycin C in mice, γH2AX levels increased until 2–4 h, followed by a monotonical decrease to the control level in the bone marrow and spleen, and increased moderately until 24 h, followed by a slight decrease by 48 h in the liver, stomach, lung and kidney. After oral administration of 400 mg/kg ethyl methanesulphonate, γH2AX levels increased until 8 h and then decreased to the control level by 24–48 h in the spleen and kidney, increased until 24 h and then slightly decreased until 48 h in the bone marrow and lung, increased until 8 h and plateaued by 48 h in the liver, and decreased until 8 h and then increased to the control level in the stomach. Both the genotoxic chemicals did not alter γH2AX levels in the testes. These results indicate that our novel method could reveal variation in the γH2AX state in mouse organs and allows monitoring of the in vivo dynamics induced by genotoxic chemicals.